Acute impact of an endurance race on cardiac function and biomarkers of myocardial injury in triathletes with and without myocardial fibrosis. (January 2020) - Tahir, Enver; Scherz, Benedikt; Starekova, Jitka; Muellerleile, Kai; Fischer, Roland; Schoennagel, Björn; Warncke, Malte; Stehning, Christian; Cavus, Ersin; Bohnen, Sebastian; Radunski, Ulf K; Blankenberg, Stefan; et al.
Aims: The aim of this study was to investigate the occurrence of myocardial injury and cardiac dysfunction after an endurance race by biomarkers and cardiac magnetic resonance in triathletes with and without myocardial fibrosis. Methods and results: Thirty asymptomatic male triathletes (45 ± 10 years) with over 10 training hours per week and 55 ± 8 ml/kg per minute maximal oxygen uptake during exercise testing were studied before (baseline) and 2.4 ± 1.1 hours post-race. Baseline cardiac magnetic resonance included cine, T1/T2, late gadolinium enhancement (LGE) and extracellular volume imaging. Post-race non-contrast cardiac magnetic resonance included cine and T1/T2 mapping. Non-ischaemic myocardial fibrosis was present in 10 triathletes (LGE+) whereas 20 had no fibrosis (LGE–). At baseline, LGE + triathletes had higher peak exercise systolic blood pressure with 222 ± 21 mmHg compared to LGE– triathletes (192 ± 30 mmHg, P < 0.01). Post-race troponin T and creatine kinase MB were similarly increased in both groups, but there was no change in T2 and T1 from baseline to post-race with 54 ± 3 ms versus 53 ± 3 ms ( P = 0.797) and 989 ± 21 ms versus 989 ± 28 ms ( P = 0.926), respectively. However, post-race left atrial ejection fraction was significantly lower in LGE + triathletes compared to LGE– triathletes (53 ± 6% vs. 59 ± 6%, P < 0.05). Furthermore, baseline atrial peak filling rates were lower in LGE – triathletes (121 ± 30 ml/s/m 2 ) compared to LGE + triathletes (161 ± 34 ml/s/m 2, P < 0.01). Post-race atrial peak filling rates increased in LGE– triathletes to 163 ± 46 ml/s/m 2, P < 0.001), but not in LGE + triathletes (169 ± 50ml/s/m 2, P = 0.747). Conclusion: Despite post-race troponin T release, we did not find detectable myocardial oedema by cardiac magnetic resonance. However, the unfavourable blood pressure response during exercise testing seemed to be associated with post-race cardiac dysfunction, which could explain the occurrence of myocardial fibrosis in triathletes.